Ethnic Disparities in the Diagnosis of Autism in Southern Israel. Issue 1 (20th October 2020) - Kerub, Orly; Haas, Eric J.; Meiri, Gal; Bilenko, Natalya; Flusser, Hagit; Michaelovski, Analya; Dinstein, Ilan; Davidovitch, Nadav; Menashe, Idan
Abstract : The prevalence of autism spectrum disorder (ASD) is continuously rising worldwide, with remarkable differences in ASD rates being reported across ethnic and socioeconomic groups. We conducted a prospective cohort study to identify the reasons for differences in ASD rates between the Bedouin and Jewish populations in southern Israel. Screening, referral, and diagnosis of toddlers aged 16–36 months were compared between Bedouin and Jewish populations. ASD screening was conducted at 35 randomly selected mother and child health centers (MCHCs) by trained nurses using the Modified Checklist for Autism in Toddlers with follow‐up (M‐CHAT/F) instrument. Toddlers screened positive at the MCHCs were monitored throughout the referral and diagnosis process at a single medical center until a diagnosis was determined by a physician specialist using DSM‐5 criteria. The study cohort comprised 3, 343 toddlers (996 Jewish and 2, 347 Bedouin). Bedouin toddlers, compared to Jewish toddlers, were less likely to screen positive with M‐CHAT/F (3.0% vs. 3.9%; P = 0.165), were significantly less likely to begin the hospital diagnosis process (HR = 0.38, 95% CI: 0.14–1.08; P = 0.068), and had a higher rates of loss‐to‐follow‐up during the hospital diagnosis process (42.9% vs. 15.6%, respectively; P = 0.001). The results suggest that ethnic‐specific barriers in the diagnosis process of ASD contribute to under‐diagnosis of ASD in the Bedouin population. Facilitating the diagnosis process for Bedouin families will help to identify more children with ASD at earlier ages and consequently close the ethnic gap in ASD rates. Lay Summary: We followed Bedouin and Jewish toddlers aged 16–36 months from southern Israel through their autism spectrum disorder (ASD) screening referral and diagnosis to identify the reasons for the differences in ASD prevalence between these ethnic groups. Jewish and Bedouin toddlers were equally identified in the ASD screening. However, Bedouin toddlers were less likely to complete the diagnosis process due to higher rates of loss‐to‐follow‐up and slower diagnosis process. Facilitating ASD diagnosis for the Bedouin population will help identifying more toddlers with ASD.